c - e uthor.9 (b, 2011)
Articles on tigers of the Sundarbans, a mangrove swamp in Bangladesh and West Bengal.
In Bengali.
Keywords: Bengal tiger -- Sundarbans (Bangladesh and India); Bengal tiger -- Conservation -- Sundarbans (Bangladesh and India); Tiger